Intergenerational transmission of trauma in Chilean exiled women in Europe - Espinoza Cartes, Carolina (Revista de Psicología, 2024)
This work is part of a research which collects the testimony of Chilean exiled women in Spain, France, Norway, Belgium, Sweden, Italy and the United Kingdom, which analyzes how the trauma of exile and its consequences, has been passed on to the following generations in the people investigated. Based on studies that have only addressed the experiences of women who have gone through processes of physical political violence (kidnapping, detention, torture) due to the persecution of the Chilean dictatorship (1973-1990), the experience of exile is addressed as human rights violation and it’s about demonstrating through their testimonies that the experience of exile has also left traces of psychological violence in the descendants of the exiles.